2018
DOI: 10.1155/2018/9091216
|View full text |Cite
|
Sign up to set email alerts
|

Current Innovations in Peripheral Nerve Stimulation

Abstract: Peripheral nerve stimulation has been used in the treatment of several chronic pain conditions including pain due to peripheral nerve dysfunctions, complex regional pain syndrome, and cranial neuralgias. It has been shown to be effective for chronic, intractable pain that is refractory to conventional therapies such as physical therapy, medications, transcutaneous electrical stimulations, and nerve blocks. Recently, a new generation of peripheral nerve stimulation devices has been developed; these allow extern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 38 publications
1
56
0
Order By: Relevance
“…Recent innovations in PNS have indicated its potential role in the treatment of intractable facial pain (Nayak and Banik, 2018). However, few studies have used PNS specifically for the management of HZO-related pain.…”
Section: Discussionmentioning
confidence: 99%
“…Recent innovations in PNS have indicated its potential role in the treatment of intractable facial pain (Nayak and Banik, 2018). However, few studies have used PNS specifically for the management of HZO-related pain.…”
Section: Discussionmentioning
confidence: 99%
“…However, PNS is different from NMES/FES, as PNS is set to stimulate the peripheral nerves and results in a mass activation of innervated muscles, as well as antidromic neuronal impulses from stimulation site, which in our protocol is set to reach the spinal cord and corticomotoneuronal synapse ( Shulga et al, 2016a , Rodionov et al, 2020 , Rodionov et al, 2019 , Tolmacheva et al, 2019a , Tolmacheva et al, 2017 ). The effect of different kinds of PNS variants has been studied in chronic pain management ( Nayak and Banik 2018 ), in post-stroke motor impairment ( Carrico et al, 2016 ) and foremost, in subacute stages of SCI where PNS has been found to be useful in one study ( Lee et al, 2015 ). However, we have been using new PNS parameters in our PAS studies, where pulses are given at 50–100 Hz and the intensity is adjusted individually based on minimal intensity inducing F-responses to ensure the activation of the motor nerves ( Shulga et al, 2016a , Shulga et al, 2016b , Rodionov et al, 2020 , Rodionov et al, 2019 , Tolmacheva et al, 2019a , Tolmacheva et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, nonnociceptive inputs are large myelinated sensory afferents that cause these gates to close and dull the sensation of pain. PNS acts on these principals and uses electrical impulses and signals to stimulate nonnociceptive large diameter fibers to close the pain gates and increase pain relief (12). Despite this ambiguity regarding the mechanism by which PNS provides pain relief, it has been used to treat brachial plexopathy of various etiologies.…”
Section: Discussionmentioning
confidence: 99%